sqrt(-3)^2 = sqrt(9) = 3

AND

sprt(-3)^2 = (sqrt(-3))^2 = (i (sqrt(3)))^2 = i^2 (sqrt(3)^2) = -1 (3) = -3

P.S. thank you for that article, I have been curious about the most efficient way to type mathematical terms for a long time B)

- Mon Sep 27, 2010 5:18 pm
- Forum: Advanced Algebra ("pre-calculus")
- Topic: Why are there two answers???
- Replies:
**3** - Views:
**2035**

sqrt(-3)^2 = sqrt(9) = 3

AND

sprt(-3)^2 = (sqrt(-3))^2 = (i (sqrt(3)))^2 = i^2 (sqrt(3)^2) = -1 (3) = -3

P.S. thank you for that article, I have been curious about the most efficient way to type mathematical terms for a long time B)

AND

sprt(-3)^2 = (sqrt(-3))^2 = (i (sqrt(3)))^2 = i^2 (sqrt(3)^2) = -1 (3) = -3

P.S. thank you for that article, I have been curious about the most efficient way to type mathematical terms for a long time B)

- Sun Sep 26, 2010 9:51 pm
- Forum: Advanced Algebra ("pre-calculus")
- Topic: Why are there two answers???
- Replies:
**3** - Views:
**2035**

It all started in my pre-calc class when my teacher gave us a packet and he had us circle an answer to a question. I'm going to save you guys some time and just say that I came up with a situation in which he couldn't give me an answer. So I figured this would be my next best option, so I really enc...